Analisis Signifikansi Taman Merdeka Kota Metro sebagai Objek Struktur Cagar Budaya - Amboro, Kian (Mahesa Research Center (PT. Mahesa Global Publishing), 2021)
This article aims to identify and analyze the Taman Merdeka Kota Metro as the object of the cultural heritage structure. This research uses a descriptive qualitative method, with historical and archaeological approaches. The results showed that the Taman Merdeka Kota Metro met the criteria for cultural heritage as stated in Article 5 and Article 8 of the Law of the Republic of Indonesia Number 11 of 2010 concerning Cultural Heritage. The criteria that are met are: a) over 50 years of age; b) represents a style period of at least 50 years; c) has a special meaning for history and education; d) have cultural values for strengthening the nation's personality; e) have a single element and become one unit with the urban spatial landscape; f) its placement is integrated with natural formations. So based on historical and archaeological perspectives, it can be concluded that Taman Merdeka Kota Metro deserves to be proposed for its status as a Cultural Heritage Structure.